ER – lysosome contacts at a pre-axonal region regulate axonal lysosome availability - Nazmiye Özkan (Nature Portfolio, 2021)
In neurons and other cells, contacts between organelles regulates function and subcellular organization, but the precise mechanisms and effects are unclear. Here the authors show that endoplasmic reticulum (ER) tubules in the soma of neurons regulate lysosome localization and function by regulating lysosomal fission, suggesting a role for ER – lysosome inter-organelle membrane contact sites in lysosomal axonal availability.